2020
DOI: 10.1017/s0272263120000029
|View full text |Cite
|
Sign up to set email alerts
|

Can Captioned Video Benefit Second Language Pronunciation?

Abstract: The present study investigated the potential benefits of extended exposure to captioned videos for second language pronunciation. We tested 90 L2 adult learners of English on speech processing skills (segmentation, speed of lexical access, and sentence processing) and phonological accuracy in perception (ABX discrimination) and production (accentedness ratings) before and after an 8-week treatment consisting of regular exposure to audiovisual materials. Participants were randomly assigned to four experimental … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 47 publications
0
21
0
Order By: Relevance
“…As regards the development of students' grammatical knowledge, Lee and Révész (2020) argue that "captions cannot only facilitate the acquisition of l2 vocabulary but also have the capacity to promote development in l2 grammatical knowledge" (p. 642). Finally, Wisniewska and Mora (2020) examine the potential benefits of captions on pronunciation, finding that they enhanced "not only the ability to segment speech, . .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…As regards the development of students' grammatical knowledge, Lee and Révész (2020) argue that "captions cannot only facilitate the acquisition of l2 vocabulary but also have the capacity to promote development in l2 grammatical knowledge" (p. 642). Finally, Wisniewska and Mora (2020) examine the potential benefits of captions on pronunciation, finding that they enhanced "not only the ability to segment speech, . .…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Recent studies have explored the benefits of using am in the efl classroom, such as the many examples of language use in real-life context they display (Peters & Muñoz, 2020;Puimège & Peters, 2020), the variety of topics they might tackle (Sert & Amri, 2021), the advantages of imagery for vocabulary learning (Webb & Rodgers, 2009a;Pujadas & Muñoz, 2020) and the possibility to use captions while viewing (Lee & Révész, 2020;Peters & Muñoz, 2020;Wisniewska & Mora, 2020). Films are usually intrinsically attractive (provided the topic appeals to the viewer) and they are said to be one of the most enjoyable and accessible forms of entertainment, which can work as a motivator and an educator for efl students (Feng & Webb, 2020), enhancing the language learning process as long as appropriate materials are selected and suitable activities designed (Donaghy, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…From the perspective of SLA, Long (2020) has argued that bi-modal and tri-modal input may improve enhanced incidental learning, an internal process in the mind of the learner that increases unconscious detection, without necessarily raising learning to the level of conscious awareness at all. Indeed, research on learning from audiovisual input has consistently shown that watching audiovisual material, especially with captions (subtitles in the L2), is beneficial for comprehension (e.g., Gass et al, 2019), vocabulary items and formulaic sequences (e.g., Peters & Webb, 2018;Pujadas & Muñoz, 2019), grammar learning (e.g., Lee & Révész, 2020;Pattemore & Muñoz, 2020), and pronunciation (Wisnieska & Mora, 2020). On the other hand, watching non-captioned video has been shown to especially benefit aural recognition of word forms (Sydorenko, 2010).…”
Section: Language Learning From Out-of-school Exposurementioning
confidence: 99%
“…In that case, raters could adopt a blocked design by randomizing files into blocks to be evaluated by different listener groups. Typically, each group rates a subset of common files shared across blocks, allowing for robust estimation of reliability, as well as a set of unique files available only to that group (see, e.g., Trofimovich et al, 2009;Wisniewska & Mora, 2020). In a completely random-raters design, each item would be evaluated by a random group of k raters, such that no two items share the same rater group.…”
Section: Approaches To the Rating Design And Proceduresmentioning
confidence: 99%